The Implementation Of Using English Movie For Improving The Students' Pronunciation At The Eleventh Grade Of SMA YAYASAN PERGURUAN KELUARGA Pematangsiantar - Bennarita Purba; Nur Hkairah Annisa (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
The aim of this research was to find out whether the implementation of using English movie effective for improving the students' pronunciation at the eleventh grade of SMA Yayasan Perguruan Keluarga Pematangsiantar in the academic year 2021/2022. This research used quantitative approach with true experimental research design. This research used saturated sampling as a technique to choose the sample and the sample of this research was 60 students. The instruments of this research were pre-test, post-test and recording. The data were taken from score of pre-test and post-test. The technique of collecting data in this research is using an oral test. The data of pre-test and post-test of both groups were analyzed by using SPSS 26.0. The result of the research shows that the testing hypothesis of post-test scores was found that the mean of post-test experimental class is 72.60 from 30 students with standard deviation 6.240 and standard error mean 1.139. Meanwhile, mean of post-test control class is 68.33 from 30 students with standard deviation 6.825 and standard error mean 1.246. And then, fcount = 6.387 > ftable = 4.01 at significance level α = 0.014 with degrees of freedom (df) = 43, it means that Ha is proven to have a significant effect in improving students' pronunciation. Then, tcount = 3.305 and ttable = 1.699. So, tcount = 3.305 > ttable = 1.699 at the significance level α = 0.05 with degrees of freedom (df) = 29. So, Ho is rejected and Ha is accepted. It means that, the implementation of using English movie effective for improving the students' pronunciation at the eleventh grade of SMA Yayasan Perguruan Keluarga Pematangsiantar